Corpos emaranhados, possibilidades de movimento, ruptura e criação: reflexões sobre subjetividade, singularidade e processos educativos - Rala, Rebeca Pereira Batalim (2017)
This research is a feminine writing that seeks to map the path of an educator and researcher involved in the search for an understanding of the politics of subjectivation that cross us, relating them to the education's territory. From a perspective of the chronogenetics (ROLNIK, 1993), memories were recovered that contained in themselves elements representative of the restlessness that moved the research and the composition of its intentions. The methodological question was constructed from the dialogue between the concepts of rhizome (DELEUZE & GUATARRI, 1995), plurality of reasons (PETERS, 2000) and cartography (KASTRUP, STEPS, SCOTLAND, 2012; ROLNIK, 2013). We sought to make the research an experience of the thought exercise, acceptance "feeling" and creation of ways and lines of escape in favor of expanding the potency of life in the territory of education and in the construction of other ways of being in the world that contemplate our needs and affections.